Investigation of the Nutrient Uptake and Cell Growth Kinetics with Monod and Moser Models for Penicillium brevicompactum ATCC 16024 in Batch Bioreactor - Fatemeh Ardestani (Iranica Journal of Energy and Environment, 2011)
In the most cases of the practical fermentation processes with filamentous microorganisms, directmonitoring of the cell morphology and biomass distribution in the culture medium is not easily possible. Useof a mathematical model is a suitable way to describe the substrate uptake and cell growth behavior of thesemicroorganisms. Penicillium brevicompactum is one of the morphologically complex filamentous fungi withdifferent structural forms. In this work, nutrient uptake and cell growth kinetics were investigated using Monodand Moser models through batch submerged fermentation in a bench-scale stirred tank bioreactor. Theexperimental data were fitted with both the Monod and the Moser kinetic with a regression value of 0.87. Themaximum specific growth rate and Monad's half-saturation coefficient were determined as 0.04 hG1 and 9 g. LG1,respectively. In Moser case, the maximum specific growth rate and K were obtained as 0.06 hG and 6.8 g. LG , s1 1respectively. Thus, both Monod and Moser kinetic are considered to be partially applicable models to explainkinetics behavior of Penicillium brevicompactum in submerged batch bioreactor culture.